Time motion differences between romanian and polish high level young soccer players during 6 vs. 6 small sided games as an effect of training program - Jastrzebski, Z.; Radziminski, L.; Stefaniak, A.; Dragos, P.; Dumitrescu, G.; Stepien, P.; Mrozik, L. (Central European Journal of Sport Sciences and Medicine, 2015)
The purpose of this study was to present a time motion differences between Romanian and Polish young soccer players during 6 vs 6 small sided games. Young male football players from Schools of Sports Masters in Oradea (Romania) and £ódŸ (Poland) participated in the study. During the training session the players participated in four smallsided games 6 vs. 6 with goalkeepers (4 × 4 min, 3 min of active recovery). Heart rate responses and distance covered during small-sided games were compared. There were significant differences in the distance covered by both nationality players and age groups in reference to each intensity zone. Polish players coverd significantly longer distance compared with romanian soccer players. The results of motion abilities of young players from two countries with different training systems show that training programs can have a significant effect on adoptive abilities of the players.